Efficacy of superimposing neuromuscular electrical stimulation onto core stability exercise in patients with nonspecific low back pain: A study protocol for a randomized controlled trial - Yongzhong Li; Qian Fang; Zhe Meng; Xuan Li; Haixin Song; Jianhua Li (PLoS ONE, 2025)
Introduction Non-specific low back pain (NSLBP) is a prevalent condition affecting individuals worldwide, leading to significant disability and healthcare costs. Traditional treatment methods have shown limited efficacy, prompting the exploration of innovative approaches. Core stability exercise (CSE) has emerged as a promising rehabilitation strategy, yet optimal activation of local muscle systems remains to be fully understood. This trial aims to assess the efficacy of superimposing neuromuscular electrical stimulation (NMES) onto CSE for improving muscle activation, function, and proprioception in NSLBP patients. Methods and analysis A total of 52 participants aged 18–60 years with NSLBP will be randomly allocated into two groups: (1) experimental group receiving NMES superimposed on CSE and (2) control group undergoing the same CSE with sham NMES. Interventions will occur three times per week for six weeks. The primary outcome measures will encompass surface electromyography (sEMG) to assess muscle activity and muscle activation timing. Secondary outcomes will include the evaluation of pain intensity using the Visual Analog Scale (VAS) and disability measured by the Oswestry Disability Index (ODI), as well as proprioception assessed through joint repositioning error (JRE) and muscle thickness evaluated via real-time ultrasound image (RUSI). Data will be collected at baseline, after six weeks, and at a six-month follow-up. A mixed ANOVA will be employed to compare differences among groups and to analyze trends over time as well as interaction effects between treatment and time. Trial registration Trial registration number: Chinese Clinical Trial Registry (ChiCTR2400092409)